Optimasi Vehicle Routing Problem pada Distribusi Tabung LPG Menggunakan Metode Ant Colony Optimization - Devitasari Simamora; Riri Syafitri Lubis; Sri Ulfa Rahayu (Universitas Negeri Gorontalo, 2026)
Inefficient distribution can increase operational costs; therefore, determining optimal routes is essential to support an efficient distribution process. This problem can be formulated as a Vehicle Routing Problem (VRP), which concerns optimizing vehicle routes from a depot to multiple destinations with minimum travel distance. This study aims to optimize the distribution route of LPG cylinders at PT Jaya Sari Artha by considering 12 distribution points. The method used is Ant Colony Optimization (ACO), a heuristic algorithm inspired by the foraging behavior of ants in finding the shortest path. The data used consist of actual travel distances between distribution points obtained from Google Maps. The results show that the implementation of ACO in the VRP model produces a distribution route with a total distance of 117.40 km, shorter than the company’s initial route of 134.50 km. Thus, a distance saving of 17.10 km or 12.72% was achieved. These findings indicate that the ACO method is effective in solving VRP and improving the efficiency of LPG cylinder distribution in a real-world case.